Successful treatment of refractory edema with traditional herbal medicine: A case report - Lee, Gayoung (Medicine (Baltimore), 2019)
RATIONALE: Refractory edema is characterized by persistent swelling which does not react to diuretic use and sodium restriction. Traditional herbal medicine, Gwack Rhyung Tang and Chunggan extract effectively treated refractory lower limb edema caused by cirrhosis and improved liver function. PATIENT CONCERNS: A 64-year-old male patient with a history of hypertension, diabetes mellitus, hepatic encephalopathy, and cellulitis presented lower limb edema which did not react to diuretics for more than 7 months. DIAGNOSES: Refractory edema caused by cirrhosis. INTERVENTIONS: The patient was treated for 25 days using Gwack Rhyung Tang and Chunggan extract. OUTCOMES: Loss of body weight, decrease in circumferences of both lower limb and improvement of liver function biochemistry results are checked. There was no recurrence or aggravation of the condition up to 3 weeks of follow-up periods. LESSONS: Traditional herbal medicine can be an effective alternative for refractory edema due to cirrhosis with improving liver function.